Exploring the Polycentric Structure and Driving Mechanism of Urban Regions From the Perspective of Innovation Network - Tang, Chenghui; Dou, Jianmin (Frontiers in Physics, 2022)
Polycentric city-regional development has become a buzzword for urban scholars and planners around the world. Inspired by the two critical characteristics of the polycentric urban region (PUR) as incubators and hinges of knowledge production, this study revealed the evolution of the polycentric structure and driving mechanism of PUR from the perspective of innovation network by using unique inter-city patent cooperation data. The results show that: (1) the innovation networks exhibit hierarchical and uneven characteristics, with the economic core cities becoming incubators and hinges of innovation and dominating the development of innovation networks. (2) There is compatibility between morphological polycentricity and functional polycentricity in PUR, but there are also differences. Although the morphological polycentricity of three PURs has improved, functional polycentricity is underdeveloped. (3) Multi-dimensional proximity such as geography, institutions, and society play a facilitating role for inter-city knowledge flows and their polycentric enhancement, but city attributes such as population size have a lower impact. Our study is believed to renew the knowledge polycentricity conceptualization and enlighten the evolution of innovation network.